What gets measured in palliative care? A review and synthesis of routine data collection in 16 countries - Johnston, Bridget (My University, 2025)
Background: There is an increasing focus on strengthening palliative care data infrastructure to evaluate and improve the quality of care. We conducted an extensive review of policy documents to identify international best practice in the use of routine data in palliative care. Methods: We identified 16 countries with well-established palliative care services before undertaking the review. We searched systematically for relevant documentation on each country in the academic, grey and governmental literature. For each country we then compiled a narrative synthesis utilising a standardised extraction template. Local experts verified country-level synopses. We combined the 16 country documents using thematic synthesis. Results: There was significant heterogeneity in the data infrastructure of the countries examined. The majority of the databases and data sources focused on specialist palliative care services with a notable lack of data on palliative care delivered in primary and community care. Several countries have established bespoke palliative care databases; others harness existing data sources, and capitalise on the existence of unique patient identifiers. The gaps and limitations identified were commonly shared across all types of palliative and end of life care data infrastructure. Similarly, many of the factors deemed highly influential in implementing and sustaining existing databases are relevant across all data infrastructure. Conclusions: This first-of-its-kind analysis details the characteristics of databases/data sources and highlights the significant heterogeneity which exists. The strengths and limitations of existing databases/data sources and the factors that influence how well these systems are sustained are examined, providing key learnings for those eager to improve the data infrastructure in their own jurisdictions.
PUBLISHED
Keywords: Big data; Palliative care; Health care systems; Comparative review